Structural characterisation of the fungal Pmt4 homodimer - McDowell, Melanie; Wild, Klemens; Fiorentino, Francesco; Bausewein, Daniela; Metschies, Anke; Chiapparino, Antonella; Hackmann, Yvonne; Bilsing, Florestan; Brenske, David; Mortensen, Sofia; Wu, Di; Robinson, Carol V.; et al. (Nature Communications, 2025)
Protein O-mannosyltransferases (PMTs) are conserved endoplasmic reticulum membrane-embedded enzymes responsible for the transfer of mannose from dolichol phosphate-mannose (Dol-P-Man) to serine/threonine-rich protein substrates or unfolded proteins. PMTs from three subfamilies form obligate dimers with different substrate specificities and require the concerted action of their transmembrane domains (TMDs) and a luminal MIR domain for catalysis. Here, we present structures, native mass spectrometry, and structure-based mutagenesis of the fungal Pmt4 homodimer. The core fold of the TMDs and MIR domain is conserved with the Pmt1-Pmt2 heterodimer, indicating a shared catalytic mechanism. Distinct from Pmt4, the MIR domain interacts in cis with the TMDs of the same subunit and has a β-hairpin insertion required for O-mannosylation of substrates. We further identify a cytosolic binding site for substrate Dol-P-Man within the Pmt4 TMDs, which is conserved amongst PMTs and important for in vivo activity. Thus, we provide a framework to understand the substrate specificity and regulation of the Pmt4 homodimer.
Veröffentlicht: 14. Dezember 2025
Gesehen am 11.02.2026